Employee retention in Malaysian Financial Institutions - Setapa, Mariam; Mustafa, Tismazammi; Mamat, Mazlina; Ramli, Nur Haslina; Muhammad Siddiq, Dedi; Saputri, Pungky Lela; Fitrianingrum, Agustina; Ab Rahman, Abdul Rahim (International Journal of Accounting, Finance and Business, 2025)
This study examines the critical factors affecting employee retention among sales employees in Malaysian financial institutions, with a specific focus on a local commercial bank. Employee retention is a significant concern for organizations due to its impact on workforce consistency and efficiency. The study aims to identify and evaluate the influence of flexible work arrangements, training and career development, compensation and benefits, and job and organization fit on employee retention. Using a quantitative research methodology, data were collected from sales teams through structured questionnaires and analyzed using statistical techniques to assess the relationships between the variables. The findings indicate that flexible work arrangements, such as telecommuting and adjustable schedules, significantly enhance employee retention. Although training and development did not show a direct correlation with retention, these factors contribute to improving employee skills and job satisfaction. Compensation and benefits were found to require regular reassessment to remain competitive and effective in retaining talent. Additionally, while job and organization fit did not exhibit a significant direct correlation with retention, it remains essential for fostering a supportive work environment. This study contributes to the existing literature by providing actionable insights for local commercial banks to develop effective retention strategies. It underscores the importance of offering flexible work options, investing in professional development, and maintaining competitive compensation packages. Future research should consider a broader range of financial institutions and incorporate advanced data analysis methods to further understand retention dynamics in the sector.